MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MELALUI MEDIA PEMBELAJARAN DI SMA MUHAMMADIYAH 4 KOTA BENGKULU - Bahrin, Bahrin; Milla, Hilyati; Putri, Misbah Diana (EDUNOMIA: Jurnal Ilmiah Pendidikan Ekonomi, 2024)
This research aims to determine the differences in the use of Microsoft PowerPoint-based learning media in improving students' critical thinking skills in class X economics subjects at SMA Muhammadiyah 4 Bengkulu City. The type of research used is quasi-experimental research. The population in this study was 35 students. Data collection techniques use observation and tests. The data analysis technique used is the t test, namely the Independent Sample Test, with the average test score in the control class being 74.4706. Meanwhile, in the experimental class the average test score was 77.5556. The data was tested using the Independent Sample T-Test. The test results show that the significant value is 0.001, which means it is smaller than (<) 0.05 based on the test decision, Ho is rejected and Ha is accepted, so it can be said that there is an average difference in students' critical thinking abilities between the control class and the experimental class. In other words, students' critical thinking abilities are better when using Microsoft Power Point-based learning media than without using learning media.